Application of the steady flamelet model on a lab-scale and an industrial furnace for different oxygen concentrations. (November 2015) - Prieler, Rene; Mayr, Bernhard; Demuth, Martin; Spoljaric, Davor; Hochenauer, Christoph
Abstract: In the present study a numerical and experimental investigation was done on the impact of oxy-fuel combustion in a lab-scale furnace. For combustion and radiation modelling the steady flamelet approach with 17 species and 25 reactions associated with a WSGG (weighted sum of grey-gases) model was used. CFD (computational fluid dynamics) model was validated by measured temperatures and heat fluxes with different O2 concentrations. It was found that simulated temperatures and heat fluxes were in close agreement with the measurements in the full range of oxygen enrichment. Although 17 species were considered the calculation time was significantly reduced by the steady flamelet approach compared to commonly used eddy dissipation concept models. Predicted and measured data revealed gas savings of 8.2% by an O2 concentration of 25 vol% instead of 21 vol%. Maximum gas savings were determined for 100 vol% O2 with a value of 16.7%. The CFD model was also applied to a simulation of an 18.2 MW walking hearth furnace under air-fired conditions which should be adapted for oxy-fuel combustion in the future. Results from CFD showed a heat flux of 9.15 MW compared to the required 9.33 MW according to the material data and production rate. Highlights: Experimental and numerical study of oxy-fuel combustion. CFD modelling of oxygen enriched combustion with detailed chemical kinetic. Reduction of calculation time using the steady flamelet approach. Increase of fuel saving and energetic efficiency due to oxygen enrichment. Application of the CFD model to an industrial walking hearth furnace.